The Relationship Between Hemorrhagic Renal Cysts and Renal Function in Polycystic Kidney Disease - Gündüz, Nesrin (Cerrahpaşa Medical Journal, 2021)
Objective: Autosomal dominant polycystic kidney disease (ADPKD) is characterized by progressive enlargement of kidneys, development of multiple cysts, and decrease in glomerular filtration rate (GFR). Total kidney volume can predict progressive kidney damage. This study investigated the relationship between hemorrhagic cysts and GFR in patients with ADPKD. Methods: Patients with ADPKD whose serum creatinine was studied in less than 1 month of computed tomography (CT) scan between 2015 and 2021 in our clinic were included. Radiologically, ADPKD was defined as the presence of 10 or more cysts larger than 5 mm in enlarged kidneys. Race, age, gender, and creatinine data of all patients were obtained from the hospital database. Estimated GFR was calculated according to the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formula. The kidney volumes and the presence of hemorrhagic cysts were recorded. Results: Overall, 114 patients [60 (52.6%) male, age 59 (44-69) years] with ADPKD were included. The creatinine, GFR, and total kidney volume were 1.25 (0.82-2.86) mg/dL, 56.5 (17.5-90.75) mL/min/1.73 m2, 916 (499-1543) mL, respectively. Hemorrhagic cyst was observed in 76 (66.7%) patients. A moderate inverse correlation was observed between total renal volume and GFR (Spearman’s rho = −0.34, P < .001). Total renal volume (P = .02) was higher and GFR (P = .009) was lower in the group with hemorrhagic cysts. When corrected for age and total renal volume, the presence of hemorrhagic cysts was independently associated with GFR. Conclusion: Hemorrhagic cyst detected by CT in patients with ADPKD is associated with reduced GFR regardless of age and kidney volume. Cite this article as: Gündüz N. The relationship between hemorrhagic renal cysts and renal function in polycystic kidney disease. Cerrahpaşa Med J. 45(3):173-176.